Assessment of effects of climate factors on diarrheal diseases at National and sub-national levels in Nepal. - Dhimal,Meghnath (2018)
SUMMARY: Global climate change is expected to increase the risk of diarrheal diseases. This study aims to assess the effects of climate factors on the incidence of diarrheal diseases of under five children in Nepal. Retrospective in nature, the study utilized climatic data from 1970 to 2014, diarrheal data between July 2002 and July 2014 and water supply and sanitation coverage data for the period 2001and 2015. Trend analysis of climatic data was done using Surfer software. Statistical modeling was carried out mainly to associate weather related variables and seasonal effects on diarrheal cases. The association between incidence of diarrhea and water supply and sanitation coverage was explored using graphical plots and spatio-temporal maps. The ethical approval to conduct this study was taken from Ethical Review Board of the Nepal Health Research Council (NHRC). General warming trend of annual maximum and minimum air temperature was observed in all five physiographic regions; Tarai, Siwaliks, Middle Mountain, High Mountain and High Himalaya. The warming rate was found higher in highlands (mountains) compared to lowlands (Tarai and Siwaliks). The country's annual maximum and minimum warming trend was 0.0368°C and 0.0146°C per year respectively. The annual precipitation trend was declining at -2.5458mm per year in all physiographic regions except High Himalayas and in all seasons except pre-monsoon. For this study, Nepal was divided into 15 Eco-Developmental regions or clusters. The ecodevelopment-wise percent rise in diarrheal cases in under-five year children per 1°C increase in average temperature ranged between 0.85% to 5.05% with highest rise detected in Western Mountain and minimum in Central Tarai. The eco-belt-wise effects was observed higher in Mountain (3.42%). The overall effect of temperature for Nepal was found to be 4.39% rise in diarrheal cases. The eco-development-wise percent rise in diarrheal cases in under-five year children per 1 cm increase in rainfall ranged between 0.40% to 0.80% with highest rise detected in Western Mountain and minimum in Central Mountain region. The eco-belt-wise effects was observed higher in Mountain (0.48%) whereas statistically insignificant in Tarai. The overall effect of rainfall for Nepal was found to be 0.28% rise in diarrheal cases. Diarrheal cases were found substantially higher in summer in ten out of the fifteen eco-development regions or clusters with 22.94% to 64.94%. The highest rise was detected in Far-Western Mountain and lowest in Western Tarai. Spring season was negatively associated in Central Hill, Mid-western Tarai and Far-western Tarai.The overall effects in Nepal due to seasonal effects were found to be 11.63% rise in summer and 14.5% less in spring compared to winter and autumn seasons as reference season combined. It is found that 0.94% to 3.50% increase in diarrheal cases in under-five children per thousand increases in the target population. The highest increase detected in Mid-western Hill and the least in Central Hill. Eco-belt-wise effects were much higher in the Mountain region (4.12%) and least in Hill (0.97%). The overall effect of population in Nepal was found to be 1.53% rise in diarrheal cases. Eco-development domain analysis disclosed that 5.98% to 20.82% increase in diarrheal cases annually with maximum found in Far-western Tarai and minimum in Far-western Hill and. Eco-beltwise effects were highest in Mountain (16.39%) and least in Tarai (12.54%). The overall effect in Nepal was found to be 13.86% annual increment.The trend of incidence of diarrheal disease among under-five children is increasing in all 15 geographical clusters across the country over the last 10 years from 2003 to 2013. Monthly diarrheal data analysis of the past 10 years (2003-2013) shows that the incidence of diarrheal diseases has occurred across all months during the year. However, in the entire geographical clusters about 60% of the diarrheal incidence took place from the months of May through October. The year 2009 has recorded the highest incidence of diarrheal disease followed by 2012 and 2013. The drinking water coverage over the past 15 years across different geographical clusters in the country was in increasing trend. However this trend was not consistent in all the clusters. The overall drinking water coverage at national level was 86%. About 14% of the drinking water sources were still unsafe for consumption but those sources were used by the people for the consumption. The computed correlation coefficient values of water coverage and incidence of diarrheal disease was found very weak indicating that the increased water coverage is not able to reduce the trend of underfive diarrheal disease incidence. Over the past 15 years, the sanitation coverage has been increased from the average of 17.7% to 90.6% from 2001 to 2015 respectively. The sanitation coverage at household level has rapidly increased from 2012 onwards. However, the sanitation coverage in the central Tarai and eastern Tarai regions is still below the average national sanitation coverage. The correlation coefficient between the sanitation coverage and diarrhea disease incidence of the under-five children shows very low positive value, indicating increased sanitation coverage has not lowered down the diarrheal disease incidence among the under-5 children population. The coverage of sanitation does not reflect the use of toilet and other behavioural aspects of total sanitation. Still there is no 100% sanitation coverage; whatever gap exist in the sanitation coverage is adequate to contaminate the overall nearby water bodies especially during first rain flush. The weather variability especially the increase in temperature favors the growth of pathogens in the contaminated water. Consumption of such contaminated water without any point of use treatment increases the incidence of diarrheal disease. Our analysis shows significant effect of air temperature and rainfall on incidence of diarrhea with wide variation across eco-development regions. The effects of climatic parameters on incidence of diarrhea are more pronounced in Mountain and Hill regions compared to Tarai region. Hence, existing diarrhea control program should be designed and updated from climate change adaptation perspective to reduce burden of diarrheal diseases among under five years children in Nepal.